Mathematics and Science Programs for the Elementary School Years. - Leiderman, Gloria F. (Review of Educational Research, 1965)
This article analyzes and evaluates the elementary school mathematics and science programs. Furthermore, the article also discusses the point of view of major curriculum projects with some reference to concept teaching and learning. There has been pressures for new mathematics curricula which necessitates an improvement in school mathematics. Several programs has been conducted in reviewing studies on curricular developments and studies of instructional materials and of children's scientific concepts. Moreover, though there have been great intellectual and technological advances which had their impact on curricular change, they have not had an equivalent impact to educational research. Finally, it is hoped that future research will continue to contribute to the advancement of the educational curricula.